2023
DOI: 10.3389/fcvm.2023.1147462
|View full text |Cite
|
Sign up to set email alerts
|

Q-VAT: Quantitative Vascular Analysis Tool

Abstract: As our imaging capability increase, so does our need for appropriate image quantification tools. Quantitative Vascular Analysis Tool (Q-VAT) is an open-source software, written for Fiji (ImageJ), that perform automated analysis and quantification on large two-dimensional images of whole tissue sections. Importantly, it allows separation of the vessel measurement based on diameter, allowing the macro- and microvasculature to be quantified separately. To enable analysis of entire tissue sections on regular labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…To assess vascular density, the Quantitative Vascular Analysis Tool (Q-VAT) 29 was utilized. The samples were placed inside the chicken egg for CAM assay, and the images were acquired using a digital microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess vascular density, the Quantitative Vascular Analysis Tool (Q-VAT) 29 was utilized. The samples were placed inside the chicken egg for CAM assay, and the images were acquired using a digital microscope.…”
Section: Methodsmentioning
confidence: 99%
“…This assay provides insights into the biological activity and neovascularization potential of each construct, through quantitative evaluation of vascular density around engineered grafts After 4 days, we observed an extensive vessel formation in the periphery of both MSOD-B and MSOD-BΔV1 eECMs (Figure 2B). Quantification of vascular densities 29 suggested a reduced vessel formation in MSOD-BΔV1 samples but without reaching significance (Figure 2C and Supplementary Figure 2A). Thus, the CAM assay indicated that both MSOD-B and MSOD-BΔV1 cartilages retain angiogenic potentials.…”
Section: Vegf Knockout Cartilage Tissues Retain Bone Remodeling Capac...mentioning
confidence: 99%